"I thought we weren't in Spain!": Discursive negotiations of realness in a foreign language classroom. (August 2021) - Whitehead, Sarah Jey
Abstract: This study examines the secluded nature of the foreign language classroom and the contrived nature of foreign language classroom discourse. A critically-inclined ecological framework positions the foreign language classroom as a complex and dynamic site, embedded in multiple social systems. Anchored in literature that situates student relationships with the foreign language as simultaneously divorced from real-world contexts and interactionally contrived, discourse analysis illuminates how classroom participants in a beginning eighth grade Spanish classroom grapple with the perceived (un)realness of the language they are using. Discourse analysis reveals regular misunderstandings between participants about the immediate realness and efficacy of Spanish, as it is used in their classroom. These moments of benign conversational conflict, referred to as boundary clashes, are valuable in the information they uncover, both about the nature of the foreign language classroom as well as about varying participant perceptions of whether Spanish is being used for practice, performance, or immediate communication.